Concerted variation of the 3′ regulatory region of Ig heavy chain and Gm haplotypes across human continental populations. Issue 4 (20th January 2020) - Frezza, Domenico; Martinez‐Labarga, Cristina; Giambra, Vincenzo; Serone, Eliseo; Scano, Giuseppina; Rickards, Olga; D'Addabbo, Pietro; Novelletto, Andrea
Abstract: Objectives: The 3′ regulatory region of the immunoglobulin heavy chain gene ( IGH ) includes the HS1.2 enhancer displaying length polymorphism with four known variants. The goal of the research was to provide an overview of this variability and of its evolutionary significance across human populations. Materials and Methods: We compiled published and original data on HS1.2 polymorphism in 3, 100 subjects from 26 human populations. Moreover, we imputed the haplotypic arrangement of the HS1.2 region in the 1000 Genomes Project (1KGP). In this dataset, imputation could also be obtained for the G1m‐G3m allotype by virtue of the precise correspondence between serological types and amino acid (and DNA) substitutions in IGHG1 and IGHG3 . Results: HS1.2 variant frequencies displayed similar patterns of continental partitioning as those reported in the literature for the physically neighboring IGHG1‐IGHG3 system. The 1KGP data revealed that linkage disequilibrium (LD) can explain the spread of joint HS1.2‐ IGHG1‐IGHG3 associations across continents and within continental populations, with stronger LD out of Africa and the features of an evolutionarily stable genomic block with differential expression in lymphoblastoid cell lines. Discussion: Strong population structuring involves at least the entire 70 kb genomic region here considered, due to the tight LD which maintained HS1.2, IGHG1, and IGHG3 in nonrandom arrangements. This might be key to better understand the evolutionary path of the entire genomic region driven by immune response capabilities, during the formation of continental gene pools.